Functionalization of [Ge9] with Small Silanes:[Ge9(SiR3)3]– (R = iBu, iPr, Et) and the Structures of (CuNHCDipp)[Ge9Si(iBu)33], (K‐18c6)Au[Ge9Si(iBu)33]2, and (K‐18c6)2[Ge9Si(iBu)32]. Issue 24 (15th November 2016) - Schiegerl, Lorenz J.; Geitner, Felix S.; Fischer, Christina; Klein, Wilhelm; Fässler, Thomas F.
Abstract : Novel silylation reactions at [Ge9 ] Zintl clusters starting from the chlorosilanes SiR3 Cl (R = i Bu, i Pr, Et) and the Zintl phase K4 Ge9 are reported. The formation of the tris‐silylated anions [Ge9 (SiR3 )3 ] – [R = i Bu (1a ), i Pr (1b ), Et (1c )] by heterogeneous reactions in acetonitrile was monitored by ESI‐MS measurements. For R = i Bu 1 H, 13 C and 29 Si NMR experiments confirmed the exclusive formation of1a . Subsequent reactions of1a with CuNHC Dipp Cl and Au(PPh3 )Cl result in formation of the neutral metal complex (CuNHC Dipp )[Ge9 Si( i Bu)3 3 ]·0.5 tol (2 ·0.5 tol) and the metal bridged dimeric unit Au[Ge9 Si( i Bu)3 3 ]2 – (3a ), isolated as a (K‐18c6) + salt in (K‐18c6)Au[Ge9 Si( i Bu)3 3 ]2 ·tol (3 ·tol), respectively. Finally, from a toluene/hexane solution of1a in presence of 18‐crown‐6, crystals of the compound (K‐18c6)2 [Ge9 Si( i Bu)3 2 ]·tol (4 ·tol), containing the bis‐silylated cluster anion [Ge9 (Si( i Bu)3 )2 ] 2– (4a ), were obtained. The compounds2 ·0.5 tol, 3 ·tol and4 ·tol were characterized by single‐crystal structure determination. Abstract :